2020
DOI: 10.3389/fendo.2020.00559
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Clinical Prediction Model Based on the Study of Risk Factors of Stroke in Patients With Type 2 Diabetes Mellitus

Abstract: Purpose: Stroke has sparked global concern as it seriously threatens people's life, bringing about dramatic health burdens on patients, especially for type 2 diabetes mellitus (T2DM) patients. Therefore, a risk scoring model is urgently valuable for T2DM patients to predict the risk of stroke incidence and for positive health intervention. Methods: We randomly divided 4,335 T2DM patients into two groups, training set ( n = 3,252) and validation set ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…What is striking is that these higher rates have been claimed to be incompletely explained by established risk factors [ 23 ]. As has been previously reported by other authors those suffering diabetes have a higher number of cardiovascular risk factors and concomitant chronic diseases [ 24 , 25 ]. Therefore, the IHM and long-term mortality rate in ischemic stroke patients with diabetes are 1.13-fold and 1.52-fold higher than in those without diabetes [ 26 ].…”
Section: Discussionsupporting
confidence: 58%
“…What is striking is that these higher rates have been claimed to be incompletely explained by established risk factors [ 23 ]. As has been previously reported by other authors those suffering diabetes have a higher number of cardiovascular risk factors and concomitant chronic diseases [ 24 , 25 ]. Therefore, the IHM and long-term mortality rate in ischemic stroke patients with diabetes are 1.13-fold and 1.52-fold higher than in those without diabetes [ 26 ].…”
Section: Discussionsupporting
confidence: 58%
“…Nomograms can generate individual probabilities of clinical events by integrating different outcome and predictor variables and merging biological information with clinical prediction models ( 33 35 ). In recent years, it has been widely used as a prediction method in clinical settings ( 36 , 37 ), and it plays a role in promoting personalized medicine ( 38 , 39 ) and facilitates physicians in predicting disease risk ( 40 ). There have been many studies on CAS prevalence and risk factors ( 4 , 41 ), but few studies on CAS risk-prediction models have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation model is improved when NRI or IDI is >0.1, which shows that the new model is superior to another. NRI analysis only considered improvement when a certain threshold was reached, while IDI analysis inspected the overall improvement of the model 30 …”
Section: Methodsmentioning
confidence: 99%